2015
DOI: 10.1039/c4ra14988b
|View full text |Cite
|
Sign up to set email alerts
|

Green synthesis of gold nanoparticles and its application for the trace level determination of painter's colic

Abstract: The green synthesis of metal nanoparticles is found to be more attractive in various disciplines, including analytical chemistry. The present study demonstrates a selective voltammetric determination of painter's colic (lead poisoning) using green synthesized gold nanoparticles (Au-NPs) modified glassy carbon electrode (GCE). The Au-NPs were synthesized by the reduction of chloroaurate ions with the fresh leaf extract of Justicia glauca. The formation of Au-NPs was confirmed by UV-visible spectroscopy using su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 44 publications
(60 reference statements)
4
9
0
Order By: Relevance
“…XRD analysis ( Figure 6 ) revealed four important peaks present in the (20–80) 2θ range. The diffraction peaks of 38.1° relates to (111), 44.5° relates to (200), 64.7° relates to (220), and 77.8° relates to (311) facets of the face center cubic (FCC) crystal lattice; these agree with reported values for similar gold nanostructures [ 69 ]. The reported peak values also matched the planes and face-centered cubic structures of AuNPs prepared by other green syntheses methods [ 22 , 70 , 71 , 72 ].…”
Section: Resultssupporting
confidence: 87%
“…XRD analysis ( Figure 6 ) revealed four important peaks present in the (20–80) 2θ range. The diffraction peaks of 38.1° relates to (111), 44.5° relates to (200), 64.7° relates to (220), and 77.8° relates to (311) facets of the face center cubic (FCC) crystal lattice; these agree with reported values for similar gold nanostructures [ 69 ]. The reported peak values also matched the planes and face-centered cubic structures of AuNPs prepared by other green syntheses methods [ 22 , 70 , 71 , 72 ].…”
Section: Resultssupporting
confidence: 87%
“…In the XRD pattern, five diffraction peaks at 2θ values of 38.43 • , 45.66 • , 65.80 • , and 78.76 • , corresponding to (111), (200), (220), and (311) crystal planes of the face-centered cubic crystal system, respectively, are seen. These results are in parallel with reported values for similar Au nanostructures [27]. EDX spectrum strongly supports the presence of gold ions.…”
Section: Resultssupporting
confidence: 91%
“…The study of XRD confirmed the presence of four significant peaks between 20 and 80 2θ range (Figure 3). The peak of diffraction observed at 77.8°, 64.7°, 44.5°and 38.1°r elated to the facets 311, 220, 200 and 111, respectively, of the face-centered cubic (FCC) crystal lattice, which are compatible with the recorded values of different gold nanostructures [27]. The recorded peak values have matched Au NP's FCC cubic structures as well as planes that were developed by other approaches of green synthesis [28][29][30][31].…”
Section: Resultssupporting
confidence: 82%